Characteristics Beyond In/Formality of Ways of Learning for Work: A Case of Knowledge-intense, Geographically-distributed Learning - Carrie P. Hunter (Adult Education Research Conference, 2011)
Pharmaceutical-sales is a knowledge-intense, highly competitive and rapidly changing industry employing a geographically distributed workforce. The varied ways in which agents in this industry continue to learn for work are presented and examined. A framework is developed and employed for exploring and reporting fundamental characteristics of ways of learning beyond designation of in/formality. Findings include the importance of peer-learning for non-co-located peers, the identification of intentional incidental learning, and a non-traditional role for workplace learning in a knowledge-intense and competitive environment.
Keywords: Knowledge-workers; geographically-distributed learning; self-directed learning; peer- learning; incidental learning